Perception of Agricultural Students towards Livestock Waste Management Education in Libya - , Fadel Ali Agila; , Hamza S. Abdalla Lagili; , Şerife Gündüz; , Williams Ndifreke Etuk; , Suleiman Mohammed Gidado (Archives of Current Research International, 2019)
Aims: The aim of this research is to define the education processes used in the management of animal wastes and the perception of Libyan agricultural students in the management of livestock wastes. Study Design: This study concentrated on the students’ population. The criteria for eligibility in this study included (i) Students of agriculture (ii) the respondent’s willingness to oblige to the study protocols and complete the study. Place and Duration of Study: The study was carried out in Tripoli University between the year 2017-2018 among cross-sectional agricultural students in Tripoli district of the Libya. Methodology: The study concentrated on students’ age less than 20-50 years, 166 male 134 female students. The associations between perception and waste management education tools and methods used in Tripoli were analyzed by means of t-test, ANOVA and descriptive statistics. The data were analyzed using the statistical software SPSS 20.0 and the reliability of the construct was examined using Cronbach’s alpha which ranged from 0.709 to 0.831 indicating excellent internal consistency. Results: The study reveal that Agricultural students in Tripoli should be experts in livestock management, by involving in planning educational programs and the delivery of these programs should offer a variety of programs to meet the need of their clients and they should facilitate participants learning processes. The agricultural students have positive perception of currently used teaching method as effective. They also have positive views about the teaching tools in livestock waste management education. There is no statistically significant difference (t (298) = -0.385, p = .700 > 0.05) between male and female agricultural students’ perception regarding the teaching tools used in education of livestock waste management. There was no statistically significant difference (t (298) = -.356, p = .722 > 0.05) between a male and female student regarding the teaching method used in education of livestock waste management. Conclusion: Best management practices, good and acceptable working conditions should be defined, as a crucial and main educational activities for educators. Continuing education and training programs appropriate to the current situation should be developed and transferred to regional educators to help the agricultural students in the area get better use of communication technologies. More teaching tools should be developed and used by livestock waste management education and teaching methods used by livestock waste management educators should be improved.